GAP ANALYSIS OF GOVERNMENT AGENCY PERFORMANCE ACCOUNTABILITY SYSTEM INDICATORS TO ACCOUNTABILITY THEORY - Sulistyo, Alan; Hestiana, Mia; Hasanah, Nurul; Sasono, Tusi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
There was no concurrent rise in the corruption perception index subsequent to the observed elevation in AKIP scores. This observation suggests that the AKIP framework has not comprehensively assessed all dimensions of the accountability theory. This article examines the disparities that exist between accountability theory and the indicators employed in the AKIP assessment. The methodology employed in this study is a comprehensive review of existing literature. The analysis yielded the discovery that multiple AKIP indicators necessitate enhancement in order to align the measurement more closely with the theory of accountability. The indicators can be classified into two distinct categories, specifically technical indicators and conceptual indicators. Technical indicators encompass a range of metrics that are utilized to assess various aspects of performance. These indicators include outcome achievement indicators, which gauge the extent to which desired outcomes have been realized. Additionally, effectiveness and efficiency indicators are employed to evaluate the degree to which objectives are met in a timely and resource-efficient manner. Periodic reporting indicators are utilized to monitor and report on progress at regular intervals. Lastly, employee professionalism indicators are used to assess the level of professionalism exhibited by individuals within an organization. Conceptual indicators encompass several key dimensions, namely transparency, liability, controllability, responsibility, and responsiveness.